2009
DOI: 10.1017/s0143385708080498
|View full text |Cite
|
Sign up to set email alerts
|

Transitive Anosov flows and Axiom-A diffeomorphisms

Abstract: Pesin sets are measurable sets along which the behavior of a matrix cocycle above a measure preserving dynamical system is explicitly controlled. In uniformly hyper-bolic dynamics, we study how often points return to Pesin sets under suitable conditions on the cocycle: if it is locally constant, or if it admits invariant holonomies and is pinching and twisting, we show that the measure of points that do not return a linear number of times to Pesin sets is exponentially small. We discuss applications to the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Notice that in this case, the geodesic flow is Anosov on the unit cotangent bundle X = T * 1 M. • The global hyperbolic structure of Anosov flows or Anosov diffeomorphisms is a very strong geometric property, so that manifolds carrying such dynamics satisfy strong topological conditions and the list of known examples is not so long. See [7] for a detailed discussion and references on that question.…”
Section: General Remarksmentioning
confidence: 99%
“…Notice that in this case, the geodesic flow is Anosov on the unit cotangent bundle X = T * 1 M. • The global hyperbolic structure of Anosov flows or Anosov diffeomorphisms is a very strong geometric property, so that manifolds carrying such dynamics satisfy strong topological conditions and the list of known examples is not so long. See [7] for a detailed discussion and references on that question.…”
Section: General Remarksmentioning
confidence: 99%
“…This generalizes Burns, Pugh and Wilkinson [5] result about the accessibility of Anosov flows. Also, as an application of Theorem 1.1 we obtain a generalization of the main result of Bonatti and Guelman [1] about the approximation of time-one maps of Anosov flows by Axiom A diffeomorphisms.…”
mentioning
confidence: 67%
“…We also give some applications to skew products (Section 5) and to Anosov diffeomorphisms (Section 6). In the case of skew products we 1 The authors jointly with Federico Rodriguez Hertz already had a proof of this result more than ten years ago.…”
mentioning
confidence: 77%
“…We point out that our proof relies on a different approach. The main inspiration for the present work comes from [BG09] where it was shown that every Axiom A discretized Anosov flow as in the hypothesis of Theorem A admits a unique attractor. By generalizing the arguments in [BG09] (see also [G02]) we are able to remove the Axiom A hypothesis and to obtain not only uniqueness of quasi-attractor but also of minimal unstable lamination.…”
Section: Introductionmentioning
confidence: 99%